ECOLOGICAL-FAUNISTICAL REVIEW OF FISH PARASITES FROM THE LAKE SOBACH’E (PUTORANA PLATEAU) - K. V. Polyaeva; V. I. Romanov (Российский паразитологический журнал, 2016)
Objective of research: The purpose of our research was to study parasite fauna of salmonoid fishes from thelakeSobach’e (Putorana plateau) and to report its ecological and faunistic characteristics.Material and methods: 88 specimens of salmonoid fishes (herring, siberian whitefish, round whitefish, arctic grayling and dominant species of char) were collected from thelakeSobach’e in July - August 2014. Collecting, fixation and cameral treatment were carried out using the standard method of Bykhovskaya-Pavlovskaya. Statistical treatment of the data was conducted using the Quantitative Parasitology 3.0 software.Results and discussion: Data on parasite infestation of salmonoid fishes from thelakeSobach’e is provided. 29 parasite species (Myxosporea – 3, Monogenea – 2, Cestoda – 7, Trematoda – 7, Nematoda – 3, Acanthocephala – 4, Hirudinea – 1, Crustacea – 2) were found. Analysis of parasite distribution in their fish hosts was described. The lake has been classified as oligotrophic with the features of subfamilies Orthocladiinae and Pontoporane according to the concept of the parasitological typing of lakes presented by Rumyantsev E.A.